Board Gender and Educational Diversity on Financial Stability In Indonesia’s Islamic Bank - Nurul Qalbi Awaliyah; Eko Albar Wahyudi; Irham Pakawaru; Sapruddin (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2025)
This study examines the effect of three dimensions: gender, educational level, and educational specialization on the board of directors (BOD) and sharia supervisory board (SSB) in Islamic banks’ financial stability. Data from 13 Islamic commercial banks in Indonesia (2015-2023) were analyzed using panel data regression with Z-score as the stability measure. Results reveal mixed effects: gender diversity on SSB and educational level diversity on BOD negatively affect bank stability, while educational specialization diversity on SSB positively contibutes to stability. Conversely, gender diversity on BOD, educational level diversity on SSB, and educational specialization diversity on BOD show no significant effects. These findings suggest that board composition characteristics have context-specific and structure-specific implications for Islamic banking stability, with business-focused expertise in supervisory functions being particularly valuable. Management should strategically evaluate board diversity dimensions beyond mere representation to enhance governance effectiveness